Respuesta :

9514 1404 393

Answer:

  (x, y) = (-6, 15) and (2, -1)

Step-by-step explanation:

You can start by subtracting the second equation from the first.

  (y) -(y) = (x^2 +2x -9) -(-2x +3)

  0 = x^2 +4x -12 . . . . . . collect terms

  0 = (x +6)(x -2) . . . . . . . factor

Solutions for x are -6 and +2. These values make the factors zero.

The corresponding solutions for y are ...

  y = -2(-6) +3 = 15

  y = -2(2) +3 = -1

Solutions to the system of equations are ...

  (x, y) = (-6, 15) and (2, -1)

Ver imagen sqdancefan